Comparison of biodiesel properties produced from moringa oleifera oil and palm oil - Ahmad Adzhim, Abdull Aziz (2014)
Continuous exploration of fossil fuel had diminished the reserve and turned the valuable non-renewable fuel into scarce. Even worse, the effect of fossil fuel combustion and volatile price had urged the scientific community to find a better substitute to a declining fossil fuel. Years of efforts had shed some light into a better solution of producing fuel from biomass source such as vegetable oils. The Moringa oleifera oil was extracted using different solvent in soxhelt extractor. The biodiesel was produced from crude palm oil and extracted Moringa oleifera oil through transesterification process using methanol and potassium hydroxide as catalyst. As a conclusion, n-Hexane was the best solvent which yielded the highest oil with an average percentage of 34.3%. The biodiesel properties of Moringa oleifera oil and palm oil such as cetane number were 66.7 and 59.5, kinematic viscosity were 4.8mm2/s and 5.03 mm2/s, cloud point were 18oC and 16oC, pour point 12oC and 7oC, flash point 165 and 160, and density 875kg/m3 and 890kg/m3. Biodiesel produced from Moringa oleifera had a potential to become a better feedstock as it possess a better properties which compare to biodiesel produce from palm oil